Interleukin-5 (IL-5) Therapy Prevents Allograft Rejection by Promoting CD4+CD25+ Ts2 Regulatory Cells That Are Antigen-Specific and Express IL-5 Receptor - Hall, Bruce M.; Hall, Rachael M.; Tran, Giang T.; Robinson, Catherine M.; Wilcox, Paul L.; Rakesh, Prateek K.; Wang, Chuanmin; Sharland, Alexandra F.; Verma, Nirupama D.; Hodgkinson, Suzanne J. (Frontiers in Immunology, 2021)
CD4+CD25+Foxp3+T cell population is heterogenous and contains three major sub-groups. First, thymus derived T regulatory cells (tTreg) that are naïve/resting. Second, activated/memory Treg that are produced by activation of tTreg by antigen and cytokines. Third, effector lineage CD4+CD25+T cells generated from CD4+CD25- T cells’ activation by antigen to transiently express CD25 and Foxp3. We have shown that freshly isolated CD4+CD25+T cells are activated by specific alloantigen and IL-4, not IL-2, to Ts2 cells that express the IL-5 receptor alpha. Ts2 cells are more potent than naïve/resting tTreg in suppressing specific alloimmunity. Here, we showed rIL-5 promoted further activation of Ts2 cells to Th2-like Treg, that expressed foxp3, irf4, gata3 and il5. In vivo, we studied the effects of rIL-5 treatment on Lewis heart allograft survival in F344 rats. Host CD4+CD25+T cells were assessed by FACS, in mixed lymphocyte culture and by RT-PCR to examine mRNA of Ts2 or Th2-like Treg markers. rIL-5 treatment given 7 days after transplantation reduced the severity of rejection and all grafts survived ≥60d whereas sham treated rats fully rejected by day 31 (p<0.01). Treatment with anti-CD25 or anti-IL-4 monoclonal antibody abolished the benefits of treatment with rIL-5 and accelerated rejection. After 10d treatment with rIL-5, hosts’ CD4+CD25+ cells expressed more Il5ra and responded to specific donor Lewis but not self. Enriched CD4+CD25+ cells from rIL-5 treated rats with allografts surviving >60 days proliferated to specific donor only when rIL-5 was present and did not proliferate to self or third party. These cells had more mRNA for molecules expressed by Th2-like Treg including Irf4, gata3 and Il5. These findings were consistent with IL-5 treatment preventing rejection by activation of Ts2 cells and Th2-like Treg.